Matharpacady-12.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
22 Matharpacady was the ancestral residence of the Miranda family. Among its members, Peter Miranda was the former principal of St. Isabel School. Under his charge, St. Isabel won accolades as one of the leading Christian Schools in the neighbourhood. He was also a piano virtuoso and the house was a venue for theatre, singing, and dancing. In 2006, Edward Miranda generously gifted the house to the Blessed Sacrament Fathers, and it was renamed Eymard Cottage.